Mapping the Information Technology (IT) governance requirements contained in the King III Report to the IT domains and processes of the Control Objectives for Information and Related Technology (COBIT) framework - Steenkamp, Gretha (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MAcc)--University of Stellenbosch, 2009.